Analisis Tingkat Literasi Digital Generasi Milenial dalam Mencegah Cyber Crime - Iffah Azzahro Aulia; Rian Vebrianto; Iqbal Miftakhul Mujtahid (Lembaga Anotero Scientific Pekanbaru, 2022)
Cybercrime is considered a serious problem in the digital age. The problem is the low literacy rate of the digital community. In Indonesia, the number of Internet users and the frequency with which people access information content and social media, especially among the millennial generation, are not accompanied by awareness to use the internet wisely. For this reason, this study aims to determine the level of digital literacy of the millennial generation in the city of Surabaya in tackling cybercrime. The research method used is a survey method with a quantitative approach. The sample used as research is 45 people from peers with a range of ages 15 to 20 years. Digital data literacy was obtained from the distribution of online questionnaires using Googleform which contained 31 statements as indicators, then analyzed descriptively using the SPSS version 23.00 program for Windows. The results showed that the level of digital literacy in general was in the low category index. The highest component is shown by Understanding Understanding, with a digital literacy index score of 46.8%, which is in the medium category. The lowest component is indicated by the ability to collaborate with a digital literacy index score of 32.2%. This research contributes in the form of new policy recommendations for policy makers as initial data screening related to digital literacy.